IgG Enzyme-linked Immunosorbent Assay (ELISA) for immunodiagnosis of Schistosoma haematobium infected subjects living in an endemic Nigerian village (2011)
Schistosoma haematobium infects school children in areas where the disease is endemic. This study was carried out to determine the reliability of IgG Enzyme-Linked Immunosorbent Assay (ELISA) as an immunodiagnostic tool, using whole antigen derived from Schistosoma eggs. Children of school going age living in Ipogun village, in south western Nigeria; a schistosomiasis endemic community; were used in this study. The sensitivity of the IgG ELISA in detecting positive cases was 68.0% and there was a significant correlation (P < 0.05) between IgG titres and the intensity of infection. However, the specificity was 59.3%, slightly lower than the sensitivity. Results from this study shows that IgG ELISA can be used as a diagnostic tool for determining S. haematobium infection, as it provides an evidence for the intensity of the infection in the infected individuals.